Simulation, prediction and driving factor analysis of ecological risk in Savan District, Laos - Xuexian, Xu; Yuling, Peng; Wenjie, Qin (Frontiers in Environmental Science, 2023)
In recent years, Laos, with its unique geographical advantages, has vigorously developed the overseas trade and cultural tourism industry, which has promoted local economic development and introduced numerous ecological and environmental problems. Therefore, this research took Savan District as the research area and built the landscape ecological risk assessment model to reveal the spatiotemporal evolution characteristics of Savan District’s ecological risk from 2000 to 2020. Then, the Geodetector model was utilized to explain the driving forces behind changes in the landscape’s ecological risk. Finally, the Markov-PLUS coupling model was used to simulate and predict the changes in the land use pattern and ecological risk in the Savan District in 2030. The following results are presented. 1) The landscape types in Savan District are mainly cultivated land and forest land, with the lowest degree of landscape fragmentation and loss, and the highest degree of landscape loss in unused land. 2) From 2000 to 2020, the average ecological risk index of the whole study area was low and showed a decreasing trend yearly, with the area of low-risk areas accounting for more than 90%. 3) In 2030, the average ecological risk index of the entire Savan region and the two provinces will rise, while the low-risk areas in the midwest regions and the high-risk areas in the northwest will increase. This study can guide the future coordinated development of the social economy and ecological environment in Savan District, Laos, and has good reference significance for ecological construction in similar areas in Southeast Asia.